Riqueza, Abundancia y Distribución de la Subfamilia Rogadinae (Hymenoptera: Braconidae) en tres ecosistemas naturales de Venezuela - Torres, Daylú N; Briceño, Rosa A (ENTOMOTROPICA, 2007)
In order to contribute abundance, richness and distribution data of the subfamily Rogadinae were made during a year collects diurnal and nocturnal with traps (yellow trays, interception, malaise, mesh, light and mixed light) at 2 times (rain and dry periods) in 3 natural ecosystems (Parque Nacional Yacambú (PNY) Lara state, Parque Nacional Guaramacal (PNG) Trujillo state y sector El Candelo (SEC) Yaracuy state); being this subfamily represented by 7 genera, 6 of which are present in the PNY: Aleiodes Wesmael, Choreborogas Whitfield, Clinocentrus Haliday, Macrostomion Szépligeti, Rogas Nees and Stiropius Cameron, 4 for the PNG: Aleiodes, Bulborogas van Achterberg, Clinocentrus and Rogas, 2 for the SEC: Aleiodes y Rogas. In relation to the abundance, of total from 323 collected individuals, 299 were of the Aleiodes genus, for which and additional study was made, obtaining 11 groups of species: albitibia, circumscriptus, dispar, gasterator, gastritor, melanopterus, pallidator, praetor, pulchripes, seriatus, and unipuntator for a total of 17 species which 4 probably are new species. Additionally 5 morfoespecies of Aleiodes outside the groups already established exist. The type of trap that collected greater number of individuals was mixed light.